Pelatihan Public Speaking Berbahasa Inggris dengan Komunitas Bekasi English Club Kota Bekasi - Reja Reja; Surfian Rahmat AP; Gema Pertiwi; Faris Widiyatmoko; Chomariyana Hesti; Hesti Rosdiana (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
The Public Speaking Training Program in English was conducted by mentioned lecturers) from Political Science Department and International Relations Department, Universitas Pembangunan Nasional Veteran Jakarta (UPNVJ through the reactivation of the English Club Reborn in Bekasi City. This is a community service initiative aimed at enhancing the English language skills of children, teenagers, and adults. In today's globalized world, proficiency in English is a vital skill that opens numerous opportunities in education and careers. Bekasi, as a rapidly developing city, has significant potential to serve as a buffer for the international city of DKI Jakarta. The long-term goal of this program is to create quality human resources ready to compete at both local and international levels. Methods to achieve these goals will include interactive classes, group discussions, and public speaking practice. Activities will be conducted regularly in the form of workshops, featuring experienced guest speakers. Additionally, the program will leverage digital technology to support learning through online platforms and social media. Expected outcomes of this program are enhanced English language skills among participants, the establishment of an active English Club community, and increased confidence in public speaking. Ultimately, this program aims to make a significant contribution to human resource development in Bekasi City. In addition, this program is also expected to become a model for education-based community development that can be replicated in other regions.